Analysis of Epidural Waveform to Determine Correct Epidural Catheter Placement After CSE Labor Analgesia - Coccoluto, Alessandra (Local Reg Anesth, 2021)
BACKGROUND: The epidural pressure is pulsatile and synchronized with arterial pulsations. Monitoring the epidural waveform has been suggested as a technique to reliably confirm the appropriate localization of the epidural catheter. OBJECTIVE: The aim of this study was to evaluate the sensitivity and specificity of the Computer Controlled Drug Delivery System with continuous pressure and waveform sensing technology (CCDDS) (CompuFlo(®) CathCheck™) as an instrument to assess the correct placement of the catheter in the epidural space in parturients who have received combined spinal-epidural technique (CSE) for labor analgesia. METHODS: We enrolled 40 consecutive healthy patients undergoing CSE labor analgesia with successful analgesia. All the cases in which pulsatile waveforms in synchrony with heart rate were detected were considered to be true positives; all the cases in which there was the absence of pulsatile waves were followed up. If these patients had to eventually relocate or manipulate the epidural catheter, they were considered to be true negative. If the absence of pulse waves was observed in the presence of successful analgesia during labor, the patients were considered to be false negatives. RESULTS: Pulsatile waveforms synchronous with heart rate were observed in 33 cases associated with adequate analgesia. In 5 cases, the pulsatile waveforms were absent due to unilateral analgesia or catheter occlusion (true negatives). In 2 cases, the patients had effective analgesia but we were not able to observe a distinct pulsatile waveform. The pressure waveform analysis through the epidural catheter had a sensitivity of 95%, a positive predictive value of 100%, a specificity of 100% and a negative predictive value of 60%. CONCLUSION: Pulsatile pressure waveform recording with CCDDS through the epidural catheter resulted in high sensitivity and positive predictive value which can help the proper placement of the epidural catheter.